Modeling of cross-shore wave propagation with moving shoreline - Cruz, Eric C. (Philippine Engineering Journal)
A numerical model for the transformation of nonlinear waves in the cross shore direction towards the shore is developed by incorporating a moving shoreline boundary condition. The shoreline formulation is based on the net volumetric change effected by the translating shoreline front. Initial numerical results indicated the need to recast the (n, u) wave model to a (n, Q) form to remove the numerical instabilities due to discretization of the physical shoreline condition. It is also imperative to apply a threshold depth at the moving front to avoid singularities due to the very small total depth at the last wet point. Subsequent numerical simulations at nonbreaking wave runup on a plane sloping beach indicate that the moving boundary treatment reproduces the important wave evolution features revealed by past analytic studies. Results of numerical simulations of wave runup rundown induced by nonlinear incident waves on beach slopes as high as 1/20 show the applicability of the moving shoreline treatment and the reformulated wave model.